Deciphering Physiological Functions of AHL Quorum Quenching Acylases - Utari, Putri D.; Vogel, Jan; Quax, Wim J. (Frontiers in Microbiology, 2017)
N-acylhomoserine lactone (AHL)-acylase (also known as amidase or amidohydrolase) is a class of enzyme that belongs to the Ntn-hydrolase superfamily. As the name implies, AHL-acylases are capable of hydrolysing AHLs, the most studied signalling molecules for quorum sensing in Gram-negative bacteria. Enzymatic degradation of AHLs can be beneficial in attenuating bacterial virulence, which can be exploited as a novel approach to fight infection of human pathogens, phytopathogens or aquaculture-related contaminations. Numerous acylases from both prokaryotic and eukaryotic sources have been characterized and tested for the interference of quorum sensing-regulated functions. The existence of AHL-acylases in a multitude of organisms from various ecological niches, raises the question of what the physiological roles of AHL-acylases actually are. In this review, we attempt to bring together recent studies to extend our understanding of the biological functions of these enzymes in nature.